Adaptation towards climate change among small scale fishermen: a comparison between the east coast and west coast fishermen in Peninsular Malaysia - Abu Samah, Asnarulkhadi; Hamdan, Mas Ernawati; Abu Samah, Bahaman; Hamzah, Azimi; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2016)
This study aims to compare the adaptation ability between the East and the West coast small scale fishermen in Peninsular Malaysia. This study is quantitative in nature whereby via a multi-stage cluster sampling, a total of 200 small scale fishermen had been selected as the respondents. The resulted analysis had confirmed that the adaptation ability are different between the East and the West coast small scale fishermen in Malaysia. Having this study offer responsible agencies opportunities to understand the adaptive ability of the fishermen, especially with regard to practice ability without putting aside their cognition and the structure abilities.